PERANCANGAN SISTEM INFORMASI PENJUALAN SPARE PART MESIN PABRIK PADA CV. REZA KARYA LESTARI BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract - CV. Reza Karya Lestari is one company that provide procurement and sales of various machinery spare parts factory. For reservations and sales of spare parts on the CV. Reza Karya Lestari still done manually, which is spread brochures and catalogs to customers through marketing. The obstacles are the information contained in brochures and catalogs are not complete, so the difficulty customers informed purchases, list any machine spare parts factory were sold and the price list offered. This study has the objective to generate sales information system web-based spare part on the CV. Reza Karya Lestari. Sales information system of machinery spare parts factory on the CV. Reza Karya Lestari can be implemented in a web form that is created with the help of application Adobe Dreamweaver. The resulting database is MySQL database with database name: reza. Consisting of staff table, table town, table products, the buyer table, table reservation, table payment, delivery table, table testimonials. Memorandum order presented in the form of pdf files that can be saved and printed as proof of booking. Likewise for booking reports, payment reports and delivery reports are also presented in the form of a pdf file. Confirmation of the transfer payment can be made via the website. Keywords - Information systems, sales, spare parts, machinery factory, web